Understanding Young Generation’s Saving Behavior: The Role of Multidimensional Financial Literacy, Materialism and Financial Inclusion - Anatasya , Putri Syifa; Innayah, Maulida Nurul (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
Saving behavior is an important aspect of personal financial management that supports individual financial stability, especially among Generation Z. This study aims to analyze the influence of financial literacy, materialism, and financial inclusion on Generation Z’s saving behavior in Banyumas Regency. This study aims to analyze the influence of financial literacy, materialism, and financial inclusion on the saving behavior of Generation Z in Banyumas Regency. Using quantitative approach, data was collected from 145 respondents using purposive sampling technique and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The results show that financial literacy has a positive and significant effect on saving behavior, while materialism and financial inclusion have no significant effect. The findings reinforce the role of multidimensional financial literacy encompassing attitudes, behaviors, and knowledge in shaping attitudes and behavioral controls that support saving habits. The practical implications of this study emphasize the importance of comprehensive financial education to shape healthy financial habits from a young age. The findings are relevant in designing national financial education policies that are more contextualized and impactful in strengthening the financial resilience of the younger generation.